Study of the distribution range of species оf the genus Adonis L. - Zhumagul, M.Zh.; Myrzagaliyeva, A.B.; Sarsembayeva, A.Sh.; Imаnova, E.M.; Zhuzzhan, K.E.; Kydyrbaeva, A.K. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
In the article data on the distribution of species of the genus Adonis L. in Kazakhstan were presented. In order to further clarify the places of distribution and inventory of modern growth of species of the genus Adonis, the main herbarium fund of botanical organizations was studied. The conducted analyses show that the highest occurrence of species is noted in Almaty region. To clarify the distribution in Kazakhstan and to compile the points of occurrence of species of the genus Adonis, 148 herbarium sheets (1843‒2021) from Al- Farabi KazNU, Institute of Botany (AA), DAPO and KIR and digital herbarium of Moscow State University (MW) were reviewed and processed. Collections from 1843 are presented. The largest number of collections is from 1940‒1972, and the main collectors are S.A. Arystangaliev, B. Bykov, N.V. Pavlov, and A.A. Ivashchenko. 148 actual places of growth for 8 Adonis species from the flora of Kazakhstan were identified: Adonis aestivalis L., Adonis apennina L. (Adonis sibirica Patr.ex Ledeb.), Adonis chrysocyathus Hook.f. & Thomson., Adonis parviflora Fisch., Adonis tianschanica (Adolf.) Lipsch., Adonis vernalis L., Adonis villosа Ledeb., Adonis volgensis Steven ex DC. Species diversity of Adonis L. is established in Dzungarian Alatau, Western Altai, Tarbagatai and Ile-Kungei Alatau, which are classified as rare and whose numbers are decreasing. Geographically, the most common are Adonis Adonis aestivalis L., Adonis parviflora Fisch. & Adonis tianschanica (Adolf.) Lipsch. The conducted research allowed systematizing, clarifying and supplementing information about species diversity and distribution of genus Adonis in the flora of Kazakhstan.
Adonis L. туысы түрлерінің таралу аймағын зерттеу
Изучение ареала распространения видов рода Аdonis L.
Keywords: distribution; herbarium; floristic regions; inventory; Kazakhstan